A comparative study on CSR disclosure between Indonesian Islamic banks and conventional banks: the application of GRI and ISR indexes - Rizki Hamdani; Yunan Najamuddin; Padma Dwi Haryanto; Muamar Nur Kholid (Jurnal Akuntansi dan Auditing Indonesia, 2020)
This study aims to determine whether or not there is a discrepancy in Corporate Social Responsibility (CSR) disclosure between sharia and conventional banks in Indonesia, and which CSR aspects are better between those two types of the banks. This study applied a quantitative approach. The analysis method used in this study to test the hypothesis was independent sample t-test. The method was applied to determine whether there is a significant difference in the average value between sharia and conventional banks. The number of samples in this study were 40 consisting of 20 Islamic banks and 20 conventional banks. The data taken were those between 2011 and 2014 which contained the information related to CSR. The results of this study indicated that there were significant differences in CSR disclosure between sharia and conventional banks. On average, CSR disclosure rate of sharia banks was higher than that of conventional banks. The weaknesses of CSR disclosure of sharia banks were in the aspects of environment and general information, while the weaknesses of CSR disclosure of conventional banks were in the aspects of energy, health and safety of the employee, product, and society involvement. Due to the limitation of this study in compiling the aspects of variables presented in Global Reporting Initiative (GRI) and Islamic Social Reporting (ISR), it is suggested for the future study to do further detail analysis to compile and to combine with the primary data in order to get the precise quality of the data disclosed by each bank.